2011
DOI: 10.1002/jca.20299
|View full text |Cite
|
Sign up to set email alerts
|

Lipid apheresis, indications, and principles

Abstract: Low-density lipoprotein apheresis (LDL apheresis) is a term that describes a group of apheresis techniques and devices that selectively remove apolipoprotein B containing lipoproteins. A number of different devices are available worldwide, which all effectively remove low-density lipoprotein cholesterol while sparing other important plasma components. LDL apheresis is used to treat familial hypercholesterolemia (FH), an inherited condition of accelerated atherosclerosis and severe coronary artery disease resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 36 publications
(82 reference statements)
1
34
0
1
Order By: Relevance
“…Two systems for whole blood lipoprotein apheresis are currently in clinical application . They are based on dextran sulfate or polyacrylate, respectively, and the polyacrylate‐based system was chosen for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Two systems for whole blood lipoprotein apheresis are currently in clinical application . They are based on dextran sulfate or polyacrylate, respectively, and the polyacrylate‐based system was chosen for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Different apheresis techniques have been developed over the years, including dextran sulphate cellulose adsorption, heparin-induced extracorporeal LDL-C precipitation, immunoadsorption and double filtration plasmapheresis [18,19,103]. The two approved methods by the FDA are the LiposorberVR system and the heparin-induced extracorporeal LDL-C precipitation system [14].…”
Section: Overview Of the Available Treatments For Hofhmentioning
confidence: 99%
“…The prevalence of heterozygous FH has been reported to be 1/217 in a recent Danish study and 1/250 in an American study using Dutch criteria for diagnosis . An accepted tool for retarding or arresting the atherosclerotic process in FH patients refractory to maximally tolerated pharmacotherapy is LDL apheresis . Beyond its lipid lowering efficacy, LDL apheresis affects several pro‐ and anti‐inflammatory factors involved in the pathophysiology of human atherosclerosis including the complement cascade, the cytokine network and several other inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…3 An accepted tool for retarding or arresting the atherosclerotic process in FH patients refractory to maximally tolerated pharmacotherapy is LDL apheresis. 4 Beyond its lipid lowering efficacy, LDL apheresis affects several pro-and anti-inflammatory factors involved in the pathophysiology of human atherosclerosis including the complement cascade, the cytokine network and several other inflammatory mediators. Several studies demonstrated the benefits of LDL apheresis on these factors, most likely due to adsorption of the mediators to the columns.…”
mentioning
confidence: 99%